Carbon-confined dual-phase coupled heterostructure composite material, preparation method and application
Patent Information
- Application Number
- CN202611147771.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-16
AI Technical Summary
其一、层间弱范德华力导致高温熔盐循环中结构坍塌粉化,电极完整性丧失;其二、单一氧化还原电对限制放电比容量,大电流放电极化严重;其三、高温长期保温易歧化分解产生惰性杂相,存储与循环稳定性差
(1)本发明提供的碳限域双相耦合异质结构复合材料V5S8/VS4@NC,以单一前驱体VS4为基础,经表面包覆和惰性气氛热处理后,获得具有双相耦合异质结构及外层碳包覆特征的复合材料。该复合材料在不破坏主体颗粒整体形貌和结构的基础上,实现了双相组分的原位构筑以及碳层的原位包覆,避免了传统机械混合方法中组分分散不均、界面结合较弱的问题,从而有利于形成稳定的异质界面和连续的导电网络。
Smart Images

Figure CN122930872A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery anode material technology, specifically to a carbon-confined dual-phase coupled heterostructure composite material, its preparation method, and its application. Background Technology
[0002] Currently, the widespread adoption of lithium-ion batteries in large-scale energy storage is limited by the relatively limited reserves of lithium resources and high manufacturing costs. In contrast, potassium resources are abundant and widely distributed, and potassium-ion batteries share a similar working mechanism with lithium-ion batteries. Therefore, potassium-ion batteries are considered a promising energy storage system.
[0003] In potassium-ion batteries, the structural stability, ion diffusion capacity, and electron transport capacity of the anode material have a significant impact on the battery's capacity, rate performance, and cycle life. Existing vanadium-based sulfide anode materials possess high theoretical capacity and abundant redox active sites. However, during repeated potassium insertion / extraction processes, the large radius of potassium ions leads to problems such as volume expansion, structural damage, particle agglomeration, and interfacial instability, resulting in rapid capacity decay and poor rate performance. Furthermore, some vanadium-based sulfide materials suffer from insufficient intrinsic conductivity and significant reaction polarization, further limiting improvements in their electrochemical performance. Application number 202511371760.8 discloses a nano-vanadium disulfide, its preparation method, and its application as a cathode material in lithium-ion batteries. The nano-vanadium disulfide exhibits a layered, sheet-like morphology, and its microstructure is used to improve the electrochemical performance of lithium-ion batteries. However, it still faces the following technical challenges: Firstly, weak van der Waals forces between layers lead to structural collapse and pulverization during high-temperature molten salt cycling, resulting in loss of electrode integrity. Secondly, a single redox couple limits the discharge specific capacity, and polarization is severe during high-current discharge. Thirdly, long-term high-temperature storage easily leads to disproportionation and decomposition, generating inert impurity phases, resulting in poor storage and cycling stability. Meanwhile, the industry generally believes that multi-vanadium-sulfur composite phases are structurally unstable at high temperatures, prone to phase decomposition and separation, and exhibit reduced conductivity. Therefore, current research focuses on single-phase vanadium sulfide compounds. Summary of the Invention
[0004] One of the objectives of this invention is to provide a carbon-confined dual-phase coupled heterostructure composite material, which improves the structural stability and electrochemical reaction kinetics performance of the composite material through the synergistic effect of the heterostructure interface and the confinement and encapsulation effect of the carbon layer.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: A carbon-confined dual-phase coupled heterostructure composite material is provided, which is a dual-phase composite structure with a tight heterostructure interface formed by the in-situ coexistence of V5S8 phase and VS4 phase. The dual-phase composite structure has an NC coating layer outside the structure, and together they form a V5S8 / VS4@NC carbon-confined dual-phase coupled heterostructure composite material.
[0006] The aforementioned carbon-confined dual-phase coupled heterostructure composite material has a VS4 phase that is a one-dimensional chain structure and a V5S8 phase that is a layered structure. The two phases interpenetrate and encapsulate each other based on VS4 to form the dual-phase composite structure.
[0007] Another object of the present invention is to provide a method for preparing the above-mentioned composite material.
[0008] The above-mentioned method for preparing a carbon-confined two-phase coupled heterostructure composite material includes the following steps in sequence: S1. Using ammonium metavanadate as the vanadium source and thioacetamide as the sulfur source, the VS4 precursor was prepared by reacting under solvothermal conditions. S2. Add the VS4 precursor to a dopamine solution and stir at room temperature to form a polydopamine coating layer on its surface, thereby obtaining the VS4@PDA precursor. S3. The VS4@PDA precursor is heated to 400~500 ℃ in an inert atmosphere and kept at that temperature for 1~2 h to convert polydopamine into a carbon layer coated structure, and at the same time, part of the VS4 in the VS4@PDA precursor is converted into another phase component V5S8, thus obtaining the product.
[0009] In the above-mentioned method for preparing a carbon-confined two-phase coupled heterostructure composite material, in step S1, under solvothermal conditions, thioacetamide slowly releases sulfur and provides a reducing environment, causing the high-valent vanadium in ammonium metavanadate to undergo sulfidation and reduction, generating V... 4+ The precursor VS4 is characterized by disulfide bonds; the molar ratio of ammonium metavanadate to thioacetamide is 1:2 to 1:10; the solvothermal reaction temperature is 150 to 220 °C, and the solvothermal reaction time is 6 to 24 h.
[0010] In the above-mentioned method for preparing a carbon-confined dual-phase coupled heterostructure composite material, in step S2, the dopamine solution refers to a solution containing dopamine or dopamine salt, and the dopamine solution also includes a buffer system; the mass ratio of VS4 precursor to dopamine solution is 1:0.2 to 1:3; the reaction system is a weakly alkaline environment with a pH of 8.0 to 9.0.
[0011] The above-mentioned method for preparing a carbon-confined biphase coupled heterostructure composite material, wherein the dopamine solution is a dopamine hydrochloride solution, the buffer system is a Tris-HCl buffer solution; the mass ratio of VS4 precursor to dopamine solution is 1:0.5 to 1:2; and the pH is 8.3 to 8.7.
[0012] The above-mentioned method for preparing a carbon-confined dual-phase coupled heterostructure composite material involves centrifuging and washing the product with deionized water and anhydrous ethanol after the surface coating reaction, and drying it at 50-80℃ for 6-12 hours to obtain the VS4@PDA precursor.
[0013] In the above-mentioned method for preparing a carbon-confined two-phase coupled heterostructure composite material, in step S3, the inert atmosphere is argon, nitrogen, or helium.
[0014] Another object of the present invention is to provide an application of the above-mentioned carbon-confined two-phase coupled heterostructure composite material.
[0015] The above-mentioned carbon-confined dual-phase coupled heterostructure composite material is used as a negative electrode material in a potassium-ion battery. The potassium-ion battery is assembled from a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a current collector, a conductive material, a binder, and the aforementioned carbon-confined dual-phase coupled heterostructure composite material. The mass ratio of the conductive material, the binder, and the aforementioned carbon-confined dual-phase coupled heterostructure composite material is 1:0.8~1.2:2.5~3.5.
[0016] The above-mentioned carbon-confined dual-phase coupled heterostructure composite material is used as a negative electrode material in potassium-ion batteries. The conductive material, binder and the carbon-confined dual-phase coupled heterostructure composite material are added to a solvent to form a slurry. The slurry is then coated onto the surface of the current collector and dried to obtain the negative electrode.
[0017] Compared with the prior art, the present invention brings the following beneficial technical effects: (1) The carbon-confined two-phase coupled heterostructure composite material V5S8 / VS4@NC provided by the present invention is based on a single precursor VS4. After surface coating and inert atmosphere heat treatment, a composite material with two-phase coupled heterostructure and outer carbon coating characteristics is obtained. This composite material realizes the in-situ construction of two-phase components and the in-situ coating of carbon layer without destroying the overall morphology and structure of the main particles. It avoids the problems of uneven component dispersion and weak interfacial bonding in traditional mechanical mixing methods, which is conducive to the formation of stable heterostructure and continuous conductive network.
[0018] (2) In the carbon-confined dual-phase coupled heterostructure V5S8 / VS4@NC composite electrode material provided by the present invention, the coupling of the two phases V5S8 and VS4 constitutes a dual-phase heterostructure. Different vanadium valence states and different sulfur chemical environments can produce synergistic effects at the interface, which is beneficial to promote charge redistribution and improve electron transport efficiency. At the same time, the outer NC coating layer in the sample contains C and N elements, which can not only improve the overall conductivity of the material, but also provide confinement, support and buffering for vanadium sulfide particles during charging and discharging, thereby alleviating the volume expansion, particle pulverization and structural collapse caused by repeated potassium ion insertion / extraction, and improving the structural stability and cycle reversibility of the material.
[0019] (3) Compared with single V5S8 or VS4 materials, the V5S8 / VS4@NC composite material of the present invention has both the function of regulating the two-phase heterogeneous interface and the function of protecting the N-doped carbon layer. On the one hand, the V5S8 / VS4 heterogeneous interface can reduce the interfacial charge transfer impedance, promote potassium ion diffusion and rapid surface energy storage reaction, and improve the rate performance of the material; on the other hand, the NC coating layer can effectively inhibit the aggregation, shedding and interfacial instability of active materials during cycling, and extend the cycle life of the material. Therefore, the composite material of the present invention has good application prospects in the field of potassium-ion battery anode materials and related electrochemical energy storage devices.
[0020] In summary, existing single-phase vanadium disulfide materials struggle to balance high conductivity and high-temperature stability. This invention overcomes the industry's preconceived notion that "composite vanadium sulfides are prone to phase separation and degradation at high temperatures." For the first time, it constructs a two-phase heterostructure with V5S8 and VS4 phases coexisting in situ. Relying on the synergistic effect of the two-phase interface, it adapts to the extreme high-temperature conditions of lithium-ion batteries, forming a complete set of technical solutions that are completely untapped by existing technologies. Attached Figure Description
[0021] Figure 1 Field emission scanning electron microscope (FESEM) image of the carbon-confined two-phase coupled heterostructure V5S8 / VS4@NC prepared in Example 1 of this invention.
[0022] Figure 2 This is a high-magnification transmission scanning electron microscope image of the carbon-confined two-phase coupled heterostructure V5S8 / VS4@NC prepared in Example 1 of the present invention.
[0023] Figure 3 The X-ray diffraction pattern of the carbon-confined two-phase coupled heterostructure V5S8 / VS4@NC prepared in Example 1 of this invention.
[0024] Figure 4 Cyclic voltammetry curves of the carbon-confined two-phase coupled heterostructure V5S8 / VS4@NC prepared in Example 1.
[0025] Figure 5Electrochemical cycling performance of the carbon-confined two-phase coupled heterostructure V5S8 / VS4@NC prepared in Example 1.
[0026] Figure 6 The X-ray diffraction pattern of a single V3S4@NC prepared for Comparative Example 1.
[0027] Figure 7 Electrochemical cycling performance of a single V3S4@NC prepared for Comparative Example 1.
[0028] Figure 8 The X-ray diffraction pattern of a single VS4 prepared for Comparative Example 2.
[0029] Figure 9 Cyclic voltammetry curves of a single VS4 prepared for Comparative Example 2.
[0030] Figure 10 The electrochemical cycling performance of a single VS4 prepared for Comparative Example 2. Detailed Implementation
[0031] This invention proposes a carbon-confined two-phase coupled heterostructure composite material, its preparation method, and its application. To make the advantages and technical solutions of this invention clearer and more explicit, the invention will be further described below with reference to specific embodiments.
[0032] All the raw materials mentioned in this invention can be purchased through commercial channels.
[0033] The main technical concept of this invention lies in addressing the problems of poor cycle stability, structural collapse, and low intrinsic conductivity of vanadium-based sulfide materials when used as anode materials in potassium-ion batteries. This invention constructs an in-situ co-existing, tightly packed heterogeneous composite material through a technical route of "VS4 precursor - VS4@PDA precursor - heterogeneous V5S8 / VS4@NC composite electrode material." The overall performance of this composite material is far superior to that of single-phase materials.
[0034] This invention discloses a method for preparing a carbon-confined biphase coupled heterostructure composite material. Ammonium metavanadate is used as the vanadium source and thioacetamide as the sulfur source, reacting under solvothermal conditions to obtain a VS4 precursor. The VS4 precursor is then added to a dopamine solution and stirred at room temperature to form a polydopamine coating layer on its surface, obtaining a VS4@PDA precursor. Subsequently, the VS4@PDA precursor is heated to 400-500 °C under an argon atmosphere and held for 1-2 h, causing the polydopamine to transform into a carbon-coated structure. Simultaneously, some of the VS4 in the precursor transforms into another phase component, ultimately obtaining a biphase coupled heterostructure composite material with carbon confinement characteristics.
[0035] Under the aforementioned solvothermal conditions, thioacetamide slowly releases sulfur and provides a reducing environment, causing the high-valent vanadium in ammonium metavanadate to undergo sulfidation and reduction, generating V... 4+ The precursor VS4, characterized by disulfide bonds, is coated with PDA to form a polydopamine coating layer. Finally, calcination is carried out to convert dopamine into a carbon layer and to convert some of VS4 into V5S8. This ensures the structural stability of the material and forms a two-phase coupled heterostructure, thereby solving the problems of poor cycle stability, easy structural collapse, and low intrinsic conductivity of vanadium-based sulfide materials when used as anode materials for potassium-ion batteries.
[0036] As a preferred embodiment of the present invention, the preparation process of the VS4 precursor is as follows: ammonium metavanadate is dissolved in a solvent to prepare a vanadium source solution, thioacetamide is dissolved in a solvent to prepare a sulfur source solution, the vanadium source solution and the sulfur source solution are mixed evenly and then transferred to a closed reaction vessel for solvothermal reaction. After the reaction is completed, the precursor is obtained by centrifugation, washing and drying.
[0037] Furthermore, the molar ratio of ammonium metavanadate to thioacetamide is 1:2 to 1:10, and more preferably 1:4 to 1:8.
[0038] Furthermore, the solvothermal reaction temperature is 150–220°C, preferably 160–200°C; the solvothermal reaction time is 6–24 h, preferably 8–18 h.
[0039] As a preferred method, the purification of the VS4 precursor involves centrifugation and washing with deionized water and anhydrous ethanol, followed by drying; the number of centrifugation and washing cycles is 2 to 5; the drying temperature is 50 to 80°C, and the drying time is 6 to 12 hours.
[0040] Preferably, the dopamine solution mentioned above refers to a solution containing dopamine or dopamine salt, and more preferably a dopamine hydrochloride solution.
[0041] Further preferably, the dopamine solution also includes a buffer system, wherein the buffer system is a Tris-HCl buffer solution; the coating reaction system is a weakly alkaline environment with a pH of 8.0 to 9.0, preferably 8.3 to 8.7.
[0042] Preferably, the mass ratio of VS4 precursor to dopamine is 1:0.2 to 1:3, more preferably 1:0.5 to 1:2; the surface coating reaction temperature is room temperature, which refers to indoor ambient temperature, generally 15 to 30°C; the stirring and coating time is 4 to 24 hours, preferably 6 to 12 hours; after the surface coating reaction is completed, the product is centrifuged and washed with deionized water and anhydrous ethanol, and dried at 50 to 80°C for 6 to 12 hours to obtain VS4@PDA precursor.
[0043] Furthermore, the inert gas includes, but is not limited to, one or more of argon, nitrogen, and helium, with argon being preferred.
[0044] Furthermore, the heat treatment temperature is 400–500℃, preferably 430–470℃; the heat treatment time is 1–2 h, preferably 1.5–2 h; and the heating rate is 1–10℃ / min, preferably 2–5℃ / min.
[0045] During the heat treatment process, dopamine-derived polydopamine is transformed into an outer N-doped carbon coating layer, which confines and supports the internal biphase active components. The composite material obtained after heat treatment includes V5S8 phase, VS4 phase and outer N-doped carbon layer, wherein the V5S8 phase and VS4 phase constitute a biphase coupled heterostructure.
[0046] The present invention also provides a carbon-confined two-phase coupled heterostructure composite material, obtained by the above preparation method.
[0047] The present invention further provides an application of a carbon-confined dual-phase coupled heterostructure composite material as a negative electrode material in potassium-ion batteries.
[0048] The aforementioned potassium-ion battery is assembled from a positive electrode, a negative electrode, an electrolyte, and a separator. The active material of the negative electrode is the aforementioned carbon-confined dual-phase coupled heterostructure composite material. Specifically, the positive electrode can be metallic potassium. Specifically, the electrolyte in the electrolyte can be potassium bis(fluorosulfonyl)imide (KFSI); the solvent can be one or more of ethylene carbonate (EC) and dimethyl carbonate (DMC). Specifically, the separator can be a glass fiber separator.
[0049] The negative electrode in a potassium-ion battery comprises a current collector, a conductive material, a binder, and a negative electrode material, wherein the negative electrode material is a carbon-confined dual-phase coupled heterostructure composite material. Specifically, the current collector can be copper foil. Specifically, the conductive material can be carbon black. Specifically, the binder can be polyvinylidene fluoride. Specifically, the mass ratio of the conductive material, binder, and carbon-confined dual-phase coupled heterostructure composite material is 1:0.8~1.2:2.5~3.5. Specifically, the conductive material, binder, and negative electrode material are added to a solvent to form a slurry, which is then coated onto the surface of the current collector and dried to obtain the final product.
[0050] The present invention will be further described below with reference to specific embodiments.
[0051] Example 1: A method for preparing a carbon-confined two-phase coupled heterostructure composite material includes the following steps: (1) Dissolve 0.5 g F127 in 30 mL of deionized water and stir magnetically at 60 °C for 20 min to obtain a homogeneous solution; add 0.35 g ammonium metavanadate to the above solution and continue stirring at 60 °C for 20 min to obtain solution A. Dissolve 1.13 g thioacetamide in 30 mL of ethylene glycol to prepare a 0.5 M thioacetamide solution to obtain solution B. After solutions A and B are completely dissolved, add solution B to solution A and continue stirring at 60 °C for 30 min to obtain a mixed solution. Transfer the obtained mixed solution to a 100 mL polytetrafluoroethylene-lined stainless steel reactor and react at 180 °C for 10 h. After the reactor cools naturally to room temperature, centrifuge the obtained precipitate and wash it three times each with deionized water and ethanol, and then dry it overnight under vacuum at 60 °C to finally obtain a black powder VS4 precursor.
[0052] (2) Prepare a 10 mM Tris-HCl buffer solution and adjust its pH to 8.5. Disperse 200 mg of the VS4 precursor obtained in step (1) in 200 mL of Tris-HCl buffer solution and sonicate for 30 min to obtain a uniform suspension. Add 200 mg of dopamine hydrochloride to the suspension and stir continuously at room temperature for 24 h to allow dopamine to undergo oxidative self-polymerization and gradually deposit on the VS4 surface. After the reaction is complete, centrifuge the obtained product and wash it multiple times with deionized water and ethanol to remove residual dopamine and buffer components. Then dry it overnight under vacuum at 60 °C to obtain a black powder VS4@PDA precursor.
[0053] (3) The black VS4@PDA precursor obtained in step (2) was placed in a magnetic boat and placed in the heating zone of a tube furnace. Under the protection of an argon atmosphere, the temperature was raised to 450°C and maintained at this temperature for 2 h. During the heat treatment, the polydopamine coating layer was carbonized in situ to form an N-doped carbon layer, and at the same time, some VS4 underwent a thermally induced phase transformation to generate the V5S8 phase. After the tube furnace was naturally cooled to room temperature, a black powdery V5S8 / VS4@NC carbon-confined dual-phase coupled heterostructure composite material was obtained.
[0054] like Figure 1 As shown, V5S8 / VS4@NC exhibits a uniform spherical shape. (Transmission electron microscopy) Figure 2 Further observation reveals the (220) crystal plane of V5S8 and the (130) crystal plane of VS4. This confirms the formation of a heterostructure in the synthesized material. Figure 3 As can be seen, all diffraction peaks correspond well to the two active components V5S8 and VS4, and no other impurities were detected, which fully proves that the above steps successfully prepared a carbon-confined two-phase coupled V5S8 / VS4 heterostructure.
[0055] Electrochemical performance testing: Using it as the negative electrode, a 2032 half-cell was assembled in a glove box filled with Ar, along with a potassium metal counter electrode, a glass fiber separator, and an electrolyte of 1.0 M potassium bis(fluorosulfonyl)imide (KFSI) in an EC:DMC ratio of 1:1 (vol%). The electrochemical performance was tested at 0.1 mV / s. -1 The scan rate and 1000 mA g -1 The current density was used to test the electrochemical performance on an electrochemical workstation and a constant current charge-discharge system.
[0056] The preparation process of the negative electrode sheet is as follows: 60 wt% V5S8 / VS4@NC, 20 wt% carbon black and 20 wt% polyvinylidene fluoride are weighed and ground in a mortar, and N-methylpyrrolidone is added dropwise and stirred until a paste is formed. The paste is then evenly coated onto copper foil and placed in a vacuum drying oven at 80°C for 12 hours.
[0057] Electrochemical test results: from CV curves ( Figure 4 V5S8 / VS4@NC electrode at 0.1 mV s -1 Cyclic voltammetry behavior indicates that the potassium storage process exhibits significant multi-step reaction characteristics, involving the synergistic effects of intercalation-type reactions and transformation-related reactions. During the first cathode scan, the prominent reduction peak at approximately 0.65 V is primarily attributed to the initial decomposition of the electrolyte, the formation of the solid electrolyte interphase (SEI) film, and K+. + Insertion-induced initial structural activation. As the potential is further reduced to the low-voltage region, the continuously increasing cathode current indicates that deep potassization has occurred, accompanied by significant structural reconstruction, suggesting that the reaction process is not limited to simple ion intercalation.
[0058] During subsequent anodic scanning, multiple oxidation peaks were observed at approximately 0.27, 1.36, 1.80, 2.27, and 2.64 V, indicating a distinct stepwise characteristic of the potassium removal process. The weaker oxidation peak at approximately 0.27 V corresponds to the presence of K+ at shallow potassium storage sites. + The deintercalation and initial deintercalation of weakly bound potassium species are involved. The oxidation peak in the intermediate potential region corresponds to the gradual depotassination and oxidation of the potassium intermediate state, while the oxidation peak in the high potential region can be attributed to the further recovery of the host framework. The presence of multiple anodic peaks indicates that the charging process involves a series of gradual structural and chemical reversals, rather than a single-step reaction.
[0059] Compared to the first cycle, the cathode and anodic responses in subsequent cycles showed a significant stabilization, and the CV curves of the second and third cycles exhibited a high degree of overlap, indicating that the electrode established a relatively reversible reaction pathway after initial activation. In particular, the cathode peak appearing at approximately 1.85 V in subsequent cycles can be attributed to a more stable and reversible potassium-based process in the activated electrode. Overall, the CV results show that the V5S8 / VS4@NC electrode undergoes significant structural evolution in the first cycle, while exhibiting better reversibility in subsequent cycles.
[0060] Depend on Figure 5 It can be seen that the charge-discharge capacity of this material in the first cycle is 523.5 and 1013.1 mAh·h / g, respectively. -1 ), in 1 A g -1 The discharge capacity shows almost no decay after 1000 cycles at a current density. The material still provides 230.8 mAh g⁻¹. -1 The material exhibits a high discharge specific capacity. This test demonstrated that the material possesses a high practical specific capacity and excellent long-term cycling performance.
[0061] Example 2: The difference from Example 1 is that in step (2), 100 mg of dopamine hydrochloride is added to the suspension.
[0062] Example 3: The difference from Example 1 is that in step (2), 400 mg of dopamine hydrochloride is added to the suspension.
[0063] Example 4: The difference from Example 1 is that in step (2), 300 mg of dopamine hydrochloride is added to the suspension.
[0064] Comparative Example 1: The difference from Example 1 is that in step (3), the black VS4@PDA precursor is placed in a magnetic boat and placed in the heating zone of a tube furnace, heated to 600°C under argon atmosphere protection, and held at this temperature for 2 h. V3S4@NC is thus prepared.
[0065] The electrochemical performance of the material prepared in Comparative Example 1 was tested, and the results are as follows: like Figure 6 As shown, all diffraction peaks correspond well to the standard card of V3S4, indicating that as the calcination temperature increases, the sulfur content of the system continues to decrease, and the product gradually evolves from a sulfur-rich phase to a vanadium-rich, sulfur-deficient phase.
[0066] Depend on Figure 7As shown, the V3S4@NC material prepared in Comparative Example 1, when used as a negative electrode material for a potassium-ion battery, exhibits charge-discharge capacities of 263.6 and 503.5 mAh / g, respectively, in the first cycle. -1 ), in 1 A g -1 After 1000 cycles at a current density, the discharge capacity is 155.89 mAh / g. -1 ).
[0067] Compared with the carbon-confined two-phase coupled heterostructure V5S8 / VS4@NC, it exhibits a larger capacity decay, indicating that the carbon-confined two-phase coupled heterostructure has better stability.
[0068] Comparative Example 2: 0.5 g of F127 was dissolved in 30 mL of deionized water and magnetically stirred at 60 °C for 20 min to obtain a homogeneous solution. 0.35 g of ammonium metavanadate was added to this solution, and stirring was continued at 60 °C for another 20 min to obtain solution A. 1.13 g of thioacetamide was dissolved in 30 mL of ethylene glycol to prepare a 0.5 M thioacetamide solution, obtaining solution B. After solutions A and B were completely dissolved, solution B was added to solution A, and stirring was continued at 60 °C for 30 min to obtain a mixed solution. The resulting mixed solution was transferred to a 100 mL PTFE-lined stainless steel reactor and reacted at 180 °C for 10 h. After the reactor cooled naturally to room temperature, the precipitate was centrifuged and washed three times each with deionized water and ethanol, then dried overnight under vacuum at 60 °C to obtain a black powder, VS4.
[0069] The electrochemical performance of the material prepared in Comparative Example 2 was tested, and the results are as follows: like Figure 8 As shown, all diffraction peaks correspond well to the standard card of VS4, indicating that the product VS4 was successfully synthesized.
[0070] like Figure 9As shown, the first three cyclic voltammetry curves of the VS4 material prepared in Comparative Example 2 as the anode material for a potassium-ion battery were measured at a scan rate of 0.1 mV / s. During the first cathode scan, significant reduction peaks appeared at approximately 1.24 V and 0.88 V, mainly related to the initial potassium ion insertion, the formation of the solid electrolyte interface film, and the deep potassiumization and structural reconstruction of the VS4 material. During the second and third cathode scans, the main reduction peaks were located at approximately 1.95 V and 1.60 V, respectively, and their positions differed significantly from those of the first reduction peak, indicating that the VS4 material underwent significant electrode activation and irreversible structural evolution during the initial potassium insertion process. During the anodic scan, oxidation peaks appeared at approximately 1.11 V, 1.41 V, and 2.29 V, mainly corresponding to the stepwise desorption of potassium ions, the gradual oxidation of the intermediate potassiumization state, and the partial recovery of the VS4 main structure. The increased overlap between the second and third cyclic voltammetry curves indicates that after the first activation, the VS4 material gradually forms a relatively stable reversible potassium storage reaction pathway; however, its redox peaks are relatively broad and the peak positions are significantly shifted, indicating that the material still exhibits significant electrochemical polarization and slow reaction kinetics.
[0071] like Figure 10 As shown, the V3S4@NC material prepared in Comparative Example 2, when used as a negative electrode material for a potassium-ion battery, exhibits charge-discharge capacities of 400.4 and 938.7 mAh / g, respectively, in the first cycle. -1 ), in 1 A g -1 After 1000 cycles at a current density, the discharge capacity is 59.34 mAh / g. -1 ).
[0072] Based on the test results of Example 1, Comparative Example 1, and Comparative Example 2, it can be seen that the V5S8 / VS4@NC carbon-confined two-phase coupled heterostructure of the present invention cannot be obtained simply by increasing the proportion of sulfur and vanadium in the raw materials or by performing conventional heat treatment on the VS4 precursor. Instead, it requires synergistic control of the precursor composition, polydopamine coating, and calcination temperature.
[0073] Specifically, Comparative Example 2, without subsequent calcination, yielded a product primarily composed of sulfur-rich single-phase VS4. Its cyclic voltammetry curves showed a significant first-cycle irreversible reaction and redox peak shift, particularly at 1 Ag... -1The low capacity after 1000 cycles indicates that simply increasing the sulfur content or retaining the high sulfur-vanadium ratio structure is insufficient to simultaneously achieve fast reaction kinetics and good cycling stability. In Comparative Example 1, the VS4@PDA precursor was calcined at 600℃. The higher temperature promoted S-S bond breakage and continuous escape of sulfur species, leading to excessive desulfurization and transformation into a single-phase V3S4@NC. Although the carbon coating provided some conductivity and structural protection, the lack of a V5S8 / VS4 two-phase heterogeneous interface resulted in significant capacity decay during long-term cycling.
[0074] In contrast, Example 1 prepared a VS4 precursor using a specific feed ratio, and after coating it with polydopamine, it was heat-treated in a temperature range of 400–500 °C. This temperature range allows some VS4 to undergo moderate desulfurization and be converted into V5S8, while retaining some incompletely converted VS4. The nitrogen-doped carbon layer formed by the pyrolysis of polydopamine can, to some extent, limit the excessively rapid escape of sulfur species and excessive grain growth, thereby achieving in-situ coupling between the V5S8 phase and the VS4 phase, and forming a two-phase heterostructure confined by an outer nitrogen-doped carbon layer.
[0075] Therefore, the formation of the biphase heterostructure of this invention depends on the synergistic effect of a specific precursor reaction ratio, polydopamine confinement coating, and a suitable calcination temperature. Without calcination, the material primarily remains a sulfur-rich single-phase VS4; when the calcination temperature is increased to 600°C, the material transforms into a single-phase V3S4 due to excessive desulfurization; only within the reaction conditions and heat treatment window of 400–500°C specified in this invention can a partial phase transformation of VS4 be controlled to obtain the V5S8 / VS4@NC carbon-confined biphase coupled heterostructure. The above comparative examples further illustrate that the raw material ratio, coating process, and calcination conditions specified in this invention are not arbitrarily chosen, but rather necessary technical conditions for forming the target biphase heterostructure and improving potassium storage performance.
[0076] Any parts not mentioned in this invention can be achieved by referring to existing technologies.
[0077] It should be noted that those skilled in the art should recognize that the above embodiments are only used to illustrate this application and are not intended to limit this application. Any appropriate changes and variations made to the above embodiments within the essential spirit and scope of this application should fall within the scope of protection of the claims of this application.
Claims
1. A carbon-confined, two-phase coupled heterostructure composite material, characterized in that, It is a two-phase composite structure formed by the in-situ coexistence of V5S8 phase and VS4 phase to form a tight heterogeneous interface. The two-phase composite structure has an NC coating layer outside the two-phase composite structure, which together form a V5S8 / VS4@NC carbon-confined two-phase coupled heterogeneous composite material.
2. The carbon-confined two-phase coupled heterostructure composite material according to claim 1, characterized in that: The VS4 phase is a one-dimensional chain structure, and the V5S8 phase is a layered structure. The two phases interpenetrate and overlap each other to form the two-phase composite structure based on VS4.
3. The method for preparing a carbon-confined two-phase coupled heterostructure composite material according to claim 1 or 2, characterized in that, The steps are as follows: S1. Using ammonium metavanadate as the vanadium source and thioacetamide as the sulfur source, the VS4 precursor was prepared by reacting under solvothermal conditions. S2. Add the VS4 precursor to a dopamine solution and stir at room temperature to form a polydopamine coating layer on its surface, thereby obtaining the VS4@PDA precursor. S3. The VS4@PDA precursor is heated to 400~500 ℃ in an inert atmosphere and kept at that temperature for 1~2 h to convert polydopamine into a carbon layer coated structure, and at the same time, part of the VS4 in the VS4@PDA precursor is converted into another phase component V5S8, thus obtaining the product.
4. The method for preparing a carbon-confined two-phase coupled heterostructure composite material according to claim 3, characterized in that, In step S1, under solvothermal conditions, thioacetamide slowly releases sulfur and provides a reducing environment, causing the high-valent vanadium in ammonium metavanadate to undergo sulfidation and reduction, generating V... 4+ The precursor VS4 is characterized by disulfide bonds; the molar ratio of ammonium metavanadate to thioacetamide is 1:2 to 1:10; the solvothermal reaction temperature is 150 to 220 °C, and the solvothermal reaction time is 6 to 24 h.
5. The method for preparing a carbon-confined two-phase coupled heterostructure composite material according to claim 3, characterized in that, In step S2, the dopamine solution refers to a solution containing dopamine or dopamine salt, and the dopamine solution also includes a buffer system; the mass ratio of VS4 precursor to dopamine solution is 1:0.2 to 1:3; the reaction system is a weakly alkaline environment with a pH of 8.0 to 9.
0.
6. The method for preparing a carbon-confined two-phase coupled heterostructure composite material according to claim 5, characterized in that, The dopamine solution is a dopamine hydrochloride solution, and the buffer system is a Tris-HCl buffer solution; the mass ratio of VS4 precursor to dopamine solution is 1:0.5 to 1:2; the pH is 8.3 to 8.
7.
7. The method for preparing a carbon-confined two-phase coupled heterostructure composite material according to claim 6, characterized in that: After the surface coating reaction was completed, the product was centrifuged and washed with deionized water and anhydrous ethanol, and dried at 50-80℃ for 6-12 h to obtain the VS4@PDA precursor.
8. The method for preparing a carbon-confined two-phase coupled heterostructure composite material according to claim 3, characterized in that: In step S3, the inert atmosphere is argon, nitrogen, or helium.
9. The application of a carbon-confined dual-phase coupled heterostructure composite material as a negative electrode material in a potassium-ion battery according to claim 1 or 2, characterized in that: The potassium-ion battery is assembled from a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a current collector, a conductive material, a binder, and the carbon-confined dual-phase coupled heterostructure composite material. The mass ratio of the conductive material, the binder, and the carbon-confined dual-phase coupled heterostructure composite material is 1:0.8~1.2:2.5~3.
5.
10. The application of the carbon-confined dual-phase coupled heterostructure composite material according to claim 9 as a negative electrode material in a potassium-ion battery, characterized in that: Conductive material, binder and the aforementioned carbon-confined dual-phase coupled heterostructure composite material are added to a solvent to form a slurry, which is then coated onto the surface of the current collector and dried to obtain the negative electrode.
Citation Information
Patent Citations
Nano vanadium disulfide, preparation method thereof and application of nano vanadium disulfide as positive electrode material in lithium thermal battery
CN121225652A